Epidemiological characteristics of brucellosis in the Omsk Region (2008-2019) - A. H. Nurpeysova; N. V. Rudakov; Yu. A. Pnevskiy; G. V. Berezkina; O. Yu. Starostina; S. Yu. Zelikman; V. V. Silaeva (Фундаментальная и клиническая медицина, 2020)
Aim. Analysis of the epidemiological and epi-zootological situation in the Omsk region over the past 12 years (2008-2019) and identification of factors affecting the epidemic manifestations of brucellosis in modern conditions on the territory of the Omsk region.Material and methods. The data of the official registration of infectious diseases in the Russian Federation, accounting documents of the Office of Rospotrebnadzor, Rosselkhoznadzor, the Main Veterinary Directorate of the Omsk Region for 2008-2019 are analyzed. A retrospective epidemiological analysis was carried out over a 12 year period. Graphic data was obtained using Microsoft Excel 2007.An analysis of 91 stationary maps of patients with newly diagnosed brucellosis was carried out.Results. Total for 2008-2019 95 cases of newly diagnosed brucellosis in humans were reported. In the study period, registration of chronic brucellosis with a gradual onset (44 cases) and residual brucellosis (13 cases) prevailed in people. Acute brucellosis was recorded in 22 cases, subacute in 8 cases. Examination of contacts in dysfunctional foci of brucellosis revealed 8 cases of latent brucellosis. Among the cases of brucellosis, residentsof the region prevailed - 84.2% (80 cases). Brucellosis in humans was recorded in 20 of 32 rural areas of the region and in the city of Omsk. In 46.3% of all newly diagnosed cases of brucellosis (44 out of 95), the professional nature of the disease was established.Conclusion. In the Omsk region in the period 2008-2019 An unfavorable situation for brucellosis remains, for many years the incidence rates have exceeded the national ones. Cases of newly diagnosed chronic and outbreaks of acute brucellosis among people continue to be recorded. Taking into account the clinical and epidemiological features and tendencies to chronicity of brucellosis infection, an increase in the number of patients requiring health and preventive measures should be expected. An objective assessment of the epidemiological situation requires a revision of the statistical forms of registration of cases of brucellosis with an indication of the clinical variants of the disease.